Lie symmetries of linear systems of two second-order ordinary differential equations - Lokaziuk, O.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
We solve the complete group classification problem for the class of normal linear systems of second-order or dinary differential equations with two dependent variables over the real field. The proof essentially uses the description of admissible transformations of this class and Lie’s theorem on realizations of Lie algebras on the line.